1996
DOI: 10.1115/1.2801169
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and Experimental Analysis of a Self-Compensating Dynamic Balancer in a Rotating Mechanism

Abstract: A theoretical and experimental approach was used to investigate the motion and effectiveness of a Self-Compensating Dynamic Balancer (SCDB). This is a device intended to minimize the effects of rotor imbalance and vibratory forces on a rotating system during normal operation. The basic concept of an automatic dynamic balancer has been described in many U.S. patents. The SCDB is composed of a circular disk with a groove containing massive balls and a low viscosity damping fluid. The objective of this research i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 2 publications
1
39
0
Order By: Relevance
“…Theoretical studies, where the ADB is modelled using equations similar to (1) and (2), can be found in Refs. [1][2][3]14,15,17]. Similarly, experimental results can be found in Refs.…”
Section: Equations Of Motionsupporting
confidence: 69%
See 1 more Smart Citation
“…Theoretical studies, where the ADB is modelled using equations similar to (1) and (2), can be found in Refs. [1][2][3]14,15,17]. Similarly, experimental results can be found in Refs.…”
Section: Equations Of Motionsupporting
confidence: 69%
“…Similarly, experimental results can be found in Refs. [14,18]. For this study we focus on the case with only two balancing masses, that is, n = 2.…”
Section: Equations Of Motionmentioning
confidence: 99%
“…However, if the mass distribution of the rotor changes then the balancing procedure may need to be repeated. This limitation motivates the study of automatic balancers that use freely moving masses to dynamically compensate for the imbalance [1].…”
Section: Introductionmentioning
confidence: 99%
“…The first study of an ABB was carried out by Thearle in 1932 [1], and the existence of a stable steady state at rotation speeds above the first critical frequency was demonstrated. More recently, the equations of motion for a planar Jeffcott rotor with an ABB have been derived using Lagrange's method [2,3,4]. In particular Green et al [4] use rotating coordinates to forge an autonomous system of governing equations.…”
Section: Introductionmentioning
confidence: 99%